Kegiatan Cooking Class Berbasis Pendekatan Montessori untuk Meningkatkan Kemandirian pada Anak Usia 4-5 Tahun - Soimah Soimah; Luthfi Aji Ramdani (ANWARUL, 2026)
Although the development of early childhood independence through hands-on activities has been widely researched, studies that specifically examine the implementation of Montessori-based cooking classes in local early childhood education contexts remain limited. This study aimed to evaluate the effectiveness of Montessori-based cooking class activities in enhancing the independence of children aged 4–5 years at KB Perintis Petir. A mixed-methods approach was employed using a Classroom Action Research design conducted over two cycles and involving 25 children selected through purposive sampling. Data were collected through behavioral observation and documentation of activities, then analyzed descriptively in both qualitative and quantitative terms using percentage scores of independence levels. The findings show a significant increase in children’s independence, as indicated by the rise in the proportion of children categorized as “Developing as Expected” and “Developing Very Well” from 32% at baseline to 100% in the second cycle. These results contribute to strengthening Montessori theory, particularly the concept of practical life, and provide practical implications for early childhood education institutions in designing experiential learning activities that support children’s independence. The study also opens opportunities for further research on the development of children’s socio-emotional aspects through structured hands-on activities.